Electrical Circuits in Biomedical Engineering Problems with Solutions - Keskin, Ali Ümit.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This authored monograph presents a comprehensive and in-depth analysis of electrical circuit theory in biomedical engineering, ideally suited as textbook for a course program. The book contains methods and theory, but the topical focus is placed on practical applications of circuit theory, including problems, solutions and case studies. The target audience primarily comprises researchers and experts in electrical engineering who intend to embark on biomedical applications. The book is also very well suited for graduate students in the field. .
Basic Concepts -- Analysis Methods -- Capacitors and First Order RC Circuits -- Inductors and First Order Rl Circuits -- Second Order Circuits and Duality -- Sinusoidal Steady-State Analysis -- Laplace Transform Methods -- Network Synthesis -- Two-Port Networks -- Operational Amplifiers .
Keywords: Biomedical engineering; Electronic circuits; Computer science -- Mathematics; Biomedical Engineering and Bioengineering; Electronic Circuits and Systems; Mathematical Applications in Computer Science